Screening for positive electrodes for magnesium batteries: a protocol for studies at elevated temperatures. Issue 84 (3rd October 2016) - Duffort, Victor; Sun, Xiaoqi; Nazar, Linda F.
Abstract : A protocol for screening of new Mg battery positive electrodes at temperatures up to 180 °C and 2 V vs. Mg enabled discovery of a high capacity conversion material, CuS. Abstract : The well-known all phenyl complex (APC) electrolyte for magnesium batteries is studied for the first time at high temperature using tetraglyme as a solvent. Combined with a molybdenum current collector, this enables the examination of positive electrode materials for Mg batteries at temperatures as high as 180 °C and up to 2 V vs. Mg, allowing discovery of the auspicious properties of CuS as a conversion cathode.